2007
DOI: 10.3354/dao075099
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive ability and sentience: Which aquatic animals should be protected?

Abstract: It is of scientific and practical interest to consider the levels of cognitive ability in animals, which animals are sentient, which animals have feelings such as pain and which animals should be protected. A sentient being is one that has some ability to evaluate the actions of others in relation to itself and third parties, to remember some of its own actions and their consequences, to assess risk, to have some feelings and to have some degree of awareness. These abilities can be taken into account when eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
104
0
16

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(120 citation statements)
references
References 79 publications
0
104
0
16
Order By: Relevance
“…Uma variação comportamental do conceito é a de que um indivíduo é senciente quando demonstra alguma habilidade para avaliar as ações dos outros, de si mesmo e de terceiros; é capaz de lembrar-se de algumas de suas ações e consequências; é capaz de avaliar riscos, possuir algum sentimento e ter algum grau de consciência 29 . Nessas diferentes definições, a senciência ou consciência dos organismos seria descrita em cinco níveis: seres inconscientes; seres com capacidade de percepção; seres com capacidade de cognição; seres com capacidade de avaliação e seres com capacidade de execução 29 .…”
Section: Legislação De Proteção Animal Para Fins Científicos E a Não unclassified
See 2 more Smart Citations
“…Uma variação comportamental do conceito é a de que um indivíduo é senciente quando demonstra alguma habilidade para avaliar as ações dos outros, de si mesmo e de terceiros; é capaz de lembrar-se de algumas de suas ações e consequências; é capaz de avaliar riscos, possuir algum sentimento e ter algum grau de consciência 29 . Nessas diferentes definições, a senciência ou consciência dos organismos seria descrita em cinco níveis: seres inconscientes; seres com capacidade de percepção; seres com capacidade de cognição; seres com capacidade de avaliação e seres com capacidade de execução 29 .…”
Section: Legislação De Proteção Animal Para Fins Científicos E a Não unclassified
“…Nessas diferentes definições, a senciência ou consciência dos organismos seria descrita em cinco níveis: seres inconscientes; seres com capacidade de percepção; seres com capacidade de cognição; seres com capacidade de avaliação e seres com capacidade de execução 29 .…”
Section: Legislação De Proteção Animal Para Fins Científicos E a Não unclassified
See 1 more Smart Citation
“…A habilidade de sentir dor é geralmente associada às capacidades de animais sencientes, sendo uma causa importante de baixo grau de bem-estar. O sistema relacionado à consciência da dor inclui uma análise cerebral complexa (BROOM, 2007). Recentemente, a ocorrência de dor em peixes tem sido debatida mais intensamente (ROSE, 2002;SNEDDON, 2002;SNEDDON et al 2003;JACKSON, 2003;CHANDROO et al, 2004; BRAITHWAITE e H U N T I N G F O R D , 2 0 0 4 ; B R A I T H WA I T E e BOULCOTT, 2007;BROOM, 2007), sendo possível perceber que ainda há muito a se pesquisar sobre a questão de como os peixes são capazes de perceber a dor e qual a intensidade dessa percepção.…”
Section: Nocicepção E Percepção Da Dorunclassified
“…Traditionally, an animal was thought to be in a better state of welfare if it demonstrated good biological functioning within its environment: good general physical health, productivity and growth. Although biological functioning is an integral part of welfare, contemporary thinking has begun to expand this definition to take into consideration an animal's mental welfare (Désiré et al, 2002;Boissy et al, 2007;Broom, 2007 . This shift in thinking is underpinned by scientific research; for example, experiments have shown some animals have the capacity for metacognition, that is they 'know what they know' and they can reflect on this knowledge to help them form decisions (Hampton, 2001).…”
mentioning
confidence: 99%